Management of chronic kidney disease and dialysis in homeless persons - Podymow, Tiina (Nature Publishing Group, 2013)
End-stage renal disease and dialysis are complicated illnesses to manage in homeless persons, who often suffer medical comorbidities, psychiatric disease, cognitive impairment and addictions; descriptions of this population and management strategies are lacking. A retrospective review of dialysis patients who were homeless or unstably housed was undertaken at an urban academic Canadian center from 2001 to 2011. Electronic hospital records were analyzed for demographic, housing, medical, and psychiatric history, dialysis history, adherence to treatment, and outcomes. Two detailed cases of homeless patients with chronic kidney disease are presented. Eleven homeless dialysis patients with a mean age of 52.7±12.3 years, mostly men and mostly from minority groups were dialyzed for 41.1±29.2 months. Most resided permanently in shelters, eventually obtained fistula access, and were adherent to dialysis schedules. Patients were often nonadherent to pre-dialysis management, resulting in emergency starts. Many barriers to care for homeless persons with end-stage kidney disease and on dialysis are identified, and management strategies are highlighted. Adherence is optimized with shelter-based health care and intensive team-oriented case management.